THE HUT ME SKIN AS TRANSITIONAL SPACE - Brigitte Rota (International Journal of Integrative Psychotherapy, 2011)
This was a keynote address delivered at the International Integrative Psychotherapy Association Conference in Vichy, France. Focus was on individual sessions and art therapy with play as a way to create a space for creation and emerging of Self.